Clinical characteristics of mephedrone toxicity reported to the UK National Poisons Information Service. Issue 8 (25th August 2010) - James, D; Adams, R D; Spears, R; Cooper, G; Lupton, D J; Thompson, J P; Thomas, S H L
Abstract : Objective: To describe the patterns and clinical features of toxicity related to recreational use of mephedrone and other cathinones in the UK using data collected by the National Poisons Information Service (NPIS). Methods: The number of accesses to TOXBASE, the NPIS online poisons information database, details of consecutive cases uploaded onto TOXBASE and the number and details of telephone enquiries made to the NPIS by health professionals in the UK were collected for the period March 2009 to February 2010. Results: Over the year of study there were 2901 TOXBASE accesses and 188 telephone enquiries relating to cathinones, the majority relating to mephedrone (TOXBASE 1664, telephone 157), with a month-on-month increase in numbers. In 131 telephone enquiries concerning mephedrone, alone or in combination with alcohol, common clinical features reported included agitation or aggression (n=32, 24%, 95% CI 18% to 33%), tachycardia (n=29, 22%, 95% CI 16% to 30%), confusion or psychosis (n=18, 14%, 95% CI 9% to 21%), chest pain (n=17, 13%, 95% CI 8% to 20%), nausea (n=15, 11%, 95% CI 7% to 18%), palpitations (n=14, 11%, 95% CI 6% to 18%), peripheral vasoconstriction (n=10, 8%, 95% CI 4% to 14%) and headache (n=7, 5%, 95% CI 2% to 11%). Convulsions were reported in four cases (3%, 95% CI 1% to 8%). One exposed person died following cardiac arrest (1%, 95% CI 0% to 4%), although subsequent investigation suggested that mephedrone was not responsible. Conclusions: Toxicity associated with recreational mephedrone use is increasingly common in the UK. Sympathomimetic adverse effects are common and severe effects are also reported. Structured data collected by the NPIS may be of use in identifying trends in poisoning and in establishing toxidromes for new drugs of abuse.